Acute toxicity test of kenikir leaf (Cosmos caudatus H.B.K) ethanolic extract on Wistar white male rats with fixed dose procedure method and its effect on histopathology of pancreatic cells - Herlina Herlina; Annisa Amriani; Indah Permata Sari; Elsa Fitria Apriani (Wolters Kluwer Medknow Publications, 2021)
In this study, acute toxicity of kenikir leaf (Cosmos caudatus HBK) ethanolic extract was conducted on Wistar white male rats with fixed dose procedure. The extraction method used was maceration using 70% ethanol. A dose of 2000 mg/kgBW was determined as the starting dose based on the preliminary test result. The rats used in the main test were divided into the normal group and the 2000 mg/kgBW dose group, each used five animals in each group. The results of the test showed that there were no deaths or toxic symptoms both of the normal group and the 2000 mg/kgBW dose group. The conducted preliminary test results a dose of 2000 mg/kgBW as the starting dose. Next, main test is done toward two groups of rats: Normal group and 2000 mg/kgBW dose group each consist of five animals. The main test results in neither deaths nor toxic symptoms from those groups. The range of toxic doses of kenikir leaf ethanolic extract that can cause acute toxicity is >2000 mg/kgBW, and hence, this experiment classified in the practically nontoxic category. Statistical analysis on effect to macroscopic organs of the liver, heart, and kidney showed no significance (P > 0.05) from kenikir leaf ethanolic extract. Average levels of biochemical parameters from the 2000 mg/kgBW group and the normal group were in the normal range. Ethanolic extract at a dose of 333 mg/kg BW does not cause severe pancreatic damage, and hence, it is considered safe for use as an antidiabetic.